Positional syncope occurring just at the right time in a patient with a permanent pacemaker: a case report - Syed Haseeb Raza Naqvi; Madiha Fatima; Pir Sheeraz Ali; Maqsood Alam; Muhammad Taha Khan; Faisal Qadir (Journal of the Pakistan Medical Association, 2021)
We present an unusual case of positional syncope occurring years after pacemaker implantation due to pacemaker lead fracture resulting from subclavian-crush syndrome. The syncope occurred incidentally during hospital admission and was timely diagnosed using an integrated approach of history taking, examination findings, device interrogation and radiographic parameters. The patient subsequently underwent lead and device revision which led to resolution of her symptoms. Continuous...